Synthesis, biological evaluation and mode of action studies of novel amidinourea inhibitors of hepatitis C virus (HCV). Issue 5 (1st March 2019) - Magri, Andrea; Mokrane, Omar; Lauder, Kate; Patel, Arvind H.; Castagnolo, Daniele
Graphical abstract: Abstract: Novel amidinourea derivatives have been synthesised and evaluated for their antiviral activity against Hepatitis C Virus (HCV). A compound with an amidinourea-spermine chemical structure, different from that of standard anti-HCV drugs, showed micromolar activity against HCV and excellent viability. Studies on the mode of action revealed that the new compound may act against HCV through the inhibition of IRES-mediated translation.